Hope in Education as Hope in Love - Zuzana Svobodová (Theology and Philosophy of Education, 2024)
Theology and Philosophy of Education is a journal dedicated to education. However, in what respect does it deal with education? What is the situation of current education? What is the main role of the school today? All articles from the first issue of the third volume of the journal Theology and Philosophy of Education are presented.